MODEL OPTIMASI PENJUALAN OLI PADA BENGKEL BARKAH JAYA MOTOR DENGAN METODE SIMPLEKS - Sahrul Juniar Arfan; Muhammad Naufal Ramadhan, Irfan Nur Arif, Paduloh (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
Optimization modeling is a method used to find the best solution to a problem from a set of possible options. This problem has not optimized complex oil sales and produced an efficient and profitable oil sales strategy for the Barkah Jaya Motor Workshop. This research aims to optimize oil sales at the Barkah Jaya Motor Workshop. This research uses the simplex method as its approach. This research discusses two types of oil, namely, Pertamina oil purchased at a price of 90,000/oil and Shell oil purchased at a price of 75,000/oil. The results of this research concluded that the optimal strategy identified was to sell 2 pcs of Pertamina oil and Shell oil to produce a maximum profit of idr 200,000